PELATIHAN DIGITAL BRANDING SEBAGAI PILIHAN DARI DIGITAL MARKETING BAGI PARA PELAKU UMKM KELURAHAN TRIWUNG LOR KOTA PROBOLINGGO - Haidiputri, Trivosa Aprilia Novadiani; Hidayati, Setyani; Febriyanti, Bella Susi; Landasari, Tri Indah; Risqina, Venanda Octa; Darmawan, Arif; Firmansyah, Niko (Abdi Panca Marga, 2023)
Technology develops every year and is utilized in various ways, including by MSME (Micro, Small, and Medium Enterprises) actors. Some people feel that technology has an impact in this era of globalization, especially the use of the internet. The internet is used as an information technology tool to carry out business activities. The goal of this activity is to create skills and creativity through digital branding in a product on digital marketing platforms (Shopee and TikTok). This training was attended by 21 MSME actors in Triwung Lor Village. MSME actors are still less innovative in developing their businesses. Generally, MSMEs do not use creative thinking in utilizing digital branding by leveraging digital platforms as marketing and sales tools. Therefore, through this training, MSME actors can become more productive in developing their businesses by following the latest trends, enabling their businesses to compete and grow in the online market world. Keywords: Digital Branding, Digital Marketing, MSMEs